IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING DUOLINGO OF THE EIGHTH GRADE AT SMPS BUDI UTOMO - Suri, Dinda; Rahmawati, Wiki Tedi; Lubis, Sofia Idawati (FKIP Universitas Al Washliyah Medan, 2024)
The study aimed to investigate the improvement of English vocabulary mastery among eighth-grade students at Budi Utomo junior high school using the Duolingo application. The research involved 41 students and used descriptive and statistical techniques to analyze data. Qualitative data was collected from interviews, observations, and documentation, while quantitative data was gathered from students' test results, both orientation and post-test. The results showed that students were enthusiastic and active in the learning process, feeling happy and discussing with each other. They easily mastered vocabulary, which influenced their test results. The statistical analysis showed an increase in students' scores from the orientation test to post-test, with a mean score of 48. The number of students achieving the KKM score also increased. In the orientation test, only 4.9% of students achieved the KKM score, but in the post-test cycle I, 87.8% of students achieved it, and in the post-test cycle II, 100% of students achieved or exceeded the KKM score. In conclusion, the Duolingo application significantly assisted students in improving their English vocabulary mastery in a fun and satisfying manner.